1987
DOI: 10.1126/science.3118465
|View full text |Cite
|
Sign up to set email alerts
|

Early Restriction of the Human Antibody Repertoire

Abstract: Diversification of the antibody repertoire in mammals results from a series of apparently random somatically propagated gene rearrangement and mutational events. Nevertheless, it is well known that the adult repertoire of antibody specificities is acquired in a developmentally programmed fashion. As previously shown, rearrangement of the gene segments encoding the heavy-chain variable regions (VH) of mouse antibodies is also developmentally ordered: the number of VH gene segments rearranged in B lymphocytes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
360
5
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(384 citation statements)
references
References 35 publications
17
360
5
2
Order By: Relevance
“…The VH1-69 immunoglobulin segment is expressed in the restricted repertoire of fetal liver B lymphocytes and is thought to be involved in natural immunity. 40,41 A productive VH1-69 rearrangement is present in ϳ1.6% of normal B lymphocytes in adults. 42 VH1-69 is rearranged in ϳ10 to 20% of B-cell chronic lymphocytic leukemia 30,43 and a VH1-69 monoclonal rearrangement is present in the majority of patients with type II mixed cryoglobulinemia, a typical HCV-related disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The VH1-69 immunoglobulin segment is expressed in the restricted repertoire of fetal liver B lymphocytes and is thought to be involved in natural immunity. 40,41 A productive VH1-69 rearrangement is present in ϳ1.6% of normal B lymphocytes in adults. 42 VH1-69 is rearranged in ϳ10 to 20% of B-cell chronic lymphocytic leukemia 30,43 and a VH1-69 monoclonal rearrangement is present in the majority of patients with type II mixed cryoglobulinemia, a typical HCV-related disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Human germline Ig V H -gene CDRs, particularly CDR1, are highly prone to R mutations We applied the computer algorithm to the analysis of the inherent Rf and R:S mutation ratio values of the CDRs and FRs of 24 selected human germline V H genes [21][22][23][24][25][26][27][28][29][30][31][32][33][34] , including H11 (Table 1). These V H genes are among those most-frequently expressed in the early and adult B-cell repertoires and encode natural antibodies and antibodies to foreign antigens, as well as autoantibodies in autoimmune patients.…”
Section: Hhs Public Accessmentioning
confidence: 99%
“…[4][5][6] In general the fetal repertoire is more restricted than the adult repertoire. [7][8][9] Several studies have shown that there are significant differences between the fetal, cord blood, and adult immunoglobulin repertoires in mice and humans. 8,[10][11][12][13][14][15][16][17][18][19][20][21] In humans, the VH4 family is represented throughout life but continues to increase as a function of age (particularly the VH4-34 and VH4-59 gene segments).…”
Section: Introductionmentioning
confidence: 99%